Persengketaan Terkait Merek Asli Dan Serupa Group Musik The Rolling Stones Dilihat Dari Prinsip First To File Dan Well Known Marks - Rinda Ayu Andieni (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This article aims to give an understanding related the protection of ownership of a work of art which is a trademark, in a way  of registration trademark ownership of certain type of goods, to indicate that the trademark has been created, produced, and owned by someone, whose application is based on rules and policies that are enforced both nationally and internationally. The writing of this article itself uses the Normative Jurisprudence research method. The conclusion of this article is to be able to better appreciate the ownership of a work of art in the form of a trademark, and to be able to understand how mechanisms and policies are applied or enforced to protect trademark rights, both individuals and business entities within the scope of a country or between countries.